Stokes to Hadamard-Rybczynski transition: an experimental investigation with argon bubbles rising in palm oil and a sigmoid integrated model for prediction - Worakrit Thida; Sorasak Danworaphong (Journal of King Saud University - Engineering Sciences, 2025)
Abstract A refined model is developed to describe the transition in bubble dynamics from the Stokes to the Hadamard-Rybczynski regime, incorporating Bond number-dependent switch terms for predictions across a wide range of Reynolds numbers. We conduct experiments on rising argon bubbles in palm oil and use the obtained data to validate the model. We also apply the proposed model to additional data deduced from related literature to demonstrate its applicability. The analysis emphasizes the role of tangential stress at the bubble surface, governed by fluid properties, bubble size, and experimental conditions, in driving the transition. This model enhances drag prediction for a given Reynolds number and is applicable in diverse industrial contexts, including bubble column design and oil recovery. It can also be integrated into numerical simulations for complex multiphase flow analysis, supporting future advancements in multiphase system modeling and applications.
Keywords: Fluid Dynamics and Mixing; Cyclone Separators and Fluid Dynamics; Electrohydrodynamics and Fluid Dynamics